PENGARUH STRATEGI BERHITUNG (DIFFERENT STRATEGIES) PADA OPERASI BILANGAN BULAT TERHADAP HASIL BELAJAR MATEMATIKA - Anugraini, Asri Putri; Patricia, Firda Alfiana (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This study aims to show the effect of counting tactics that will occur when students study student mathematics. The method used in this study used a quasi-experimental method with a research design of Two Group Randomized Subject Posttest Only. Research activities at SD 4 Panggungrejo Kepanjen were carried out from 16 August to 5 October 2022 for second-grade students at SD 4 Panggungrejo Kepanjen. The sample used was 17 students in 2A grade as the experimental class and 20 students in 2B grade as the control group. The research instrument used was a learning achievement test. The research instrument used was a learning achievement test. The data analysis technique in this study used the t-test to test the proposed hypothesis. The results obtained were counted as much as 0.606 and then consulted using a significance level of 0.05 and 35 degrees of freedom obtained a ttable value of 1.6897. The value of tcount < ttable (0.606 <1.6897) then H0 is accepted, as a result there will be no disparity that will occur in students' mathematics learning between classes taught with arithmetic strategies compared to students with techniques using traditional algorithms. In conclusion, there is no effect of learning the art of arithmetic management on students' mathematics learning outcomes.